2018
DOI: 10.1371/journal.pone.0200796
|View full text |Cite
|
Sign up to set email alerts
|

Signs of continental ancestry in urban populations of Peru through autosomal STR loci and mitochondrial DNA typing

Abstract: The human genetic diversity around the world was studied through several high variable genetic markers. In South America the demic consequences of admixture events between Native people, European colonists and African slaves have been displayed by uniparental markers variability. The mitochondrial DNA (mtDNA) has been the most widely used genetic marker for studying American mixed populations, although nuclear markers, such as microsatellite loci (STRs) commonly used in forensic science, showed to be genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The presence of se 302 , se 428 , Se 357,739,960 may suggest gene flows from Europeans, Africans, and South Asians to this population. However, recent studies suggested that no apparent gene flows from South Asians to this population occurred . In addition, although se 302 is prevalent in South Asians, this allele is also detected in some other populations with quite low frequency, for example, Europeans from Northern Portugal and Kenyans but not other admixed Americans (1000 Genomes Consortium Phase 3 data).…”
Section: Discussionmentioning
confidence: 72%
“…The presence of se 302 , se 428 , Se 357,739,960 may suggest gene flows from Europeans, Africans, and South Asians to this population. However, recent studies suggested that no apparent gene flows from South Asians to this population occurred . In addition, although se 302 is prevalent in South Asians, this allele is also detected in some other populations with quite low frequency, for example, Europeans from Northern Portugal and Kenyans but not other admixed Americans (1000 Genomes Consortium Phase 3 data).…”
Section: Discussionmentioning
confidence: 72%
“…The separation and detection were conducted with an Applied Biosystems ® 3130xl Genetic Analyzer (Thermo Fisher Scientific, Waltham, MA, USA) according to manufacturer's protocols [12,18]. The collection and the analysis of the data obtained by capillary electrophoresis were assessed by GeneMapper ® software v.1.4 (Applied Biosystems, Waltham, MA, USA) [19,20]. To evaluate concordance, conventional DNA testing and allele calls were compared to the results of the ANDE System [12].…”
Section: Methodsmentioning
confidence: 99%
“…[11,17,18]. In Peru, with few exceptions [19,20], published autosomal STR reference data are scarce and available mostly from large cosmopolitan areas (e.g. Lima, Trujillo).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, forensic genetic parameters were also calculated for the combined set from the Northeastern Peruvian Andes. To gain a better insight of the possible genetic subdivision in Peru, we characterize the genetic differentiation between our rural Northeastern Peruvian Andes set and that of the admixed cosmopolitan populations described in [19,21].…”
Section: Introductionmentioning
confidence: 99%